Usulan Klasifikasi ABC dan Penerapan 5R Terhadap Efisiensi Waktu Kerja Pada Gudang Arsip di PT. XYZ - Vendhi Prasmoro, Alloysius; A. Nuryamin; Nuryono, Arif (Program Studi Teknik Industri, Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2021)
XYZ is a company engaged in stamping & tools that produces various product components for 4 (four) wheeled vehicles. The high time to search for archives in a messy archive warehouse causes time wastage which results in increased labor costs so that repairs need to be made using the ABC classification method and the application of 5R. The company managed to rearrange the messy archive warehouse into a tidier and efficient working time from 58 minutes to 27 minutes or 53.4% and resulted in a decrease in labor costs with a value of Rp. 14,105.00 or 53.4%..